Perfect ghost [large type] - Barnes, Linda (Center Point Large Print, 2013)
Mousy and shy to the point of agoraphobic, Em Moore is the writing half of a celebrity biography team. Her charismatic partner, Teddy, does the interviewing and the public schmoozing. But her dependence on Teddy runs deeper than just the job. Teddy is her bridge to the world and the main source of love in her life. So when Teddy dies in a car accident, Em is devastated, alone in a world she does not understand. The only way she can honor his memory and cope with his loss is to finish the interviews for their current book, an autobiography of renowned and reclusive film director Garrett Malcolm. Ensconced in a small cottage near his Cape Cod home, Em slowly builds the courage to interview Malcolm the way Teddy would have. She finds Malcolm at once friendlier, more intimidating, and much sexier than she had imagined. But Em soon starts hearing whispers of skeletons in the Malcolm family closet. And then the police begin looking into the accident that killed Teddy, and her control on her life, tenuous at best, is threatened.